2019
DOI: 10.1002/app.48486
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties and self‐healing behavior of PNIPAM nanocomposite hydrogel by using POSS as a physical crosslinker

Abstract: In this study, water-soluble octa(3-chloroammoniumpropyl) silsesquioxane (OCAPS) was found to aggregate into nanoparticles with a positive charge in solution, which can attract persulfate anion radical to initiate N-isopropylacrylamide monomers. Due to the electrostatic and hydrogen bond interaction between OCAPS and poly(N-isopropylacrylamide) (PNIPAM) chain, OCAPS can act as an effective physical crosslinker to result in a nanocomposite hydrogel (OCAPS-PNIPAM) with very small loading N, N 0 -methylene-bisacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The spectrum of PDA.0 has characteristic signals at 3431 cm −1 (OH and NH stretching mode), 2840–3000 cm −1 (CH stretching modes), and two signals at 1633 cm −1 (C═O stretching mode) and 1538 cm −1 (NH bending mode). [ 25–27 ] With increasing PDA coating on the hydrogels, these FT‐IR signals are overlaid by characteristic PDA absorbance peaks at 3172 cm −1 (phenolic OH and NH stretching modes), 1506 cm −1 (NH bending modes), and 1273 cm −1 (phenolic CO stretching modes), also confirming the successful PDA surface coating strategy. [ 28,29 ]…”
Section: Resultsmentioning
confidence: 85%
“…The spectrum of PDA.0 has characteristic signals at 3431 cm −1 (OH and NH stretching mode), 2840–3000 cm −1 (CH stretching modes), and two signals at 1633 cm −1 (C═O stretching mode) and 1538 cm −1 (NH bending mode). [ 25–27 ] With increasing PDA coating on the hydrogels, these FT‐IR signals are overlaid by characteristic PDA absorbance peaks at 3172 cm −1 (phenolic OH and NH stretching modes), 1506 cm −1 (NH bending modes), and 1273 cm −1 (phenolic CO stretching modes), also confirming the successful PDA surface coating strategy. [ 28,29 ]…”
Section: Resultsmentioning
confidence: 85%
“…The resultant hydrogels were highlighted with antibacterial property due to the synergistic effect of EDTA and OAPOSS. Zhang et al offered an interesting model for the incorporation of OAPOSS into PNIPAM hydrogels via FRP initiated KPS/TMEDA at room temperature with very small amount of chemical crosslinker BIS . As OAPOSS could aggregate into positive-charged nanoparticles in aqueous solution, they would attract persulfate anion radical by ionic interaction and then function as multifunctional initiation sites for monomers, which ultimately became physical crosslinking points and were stabilized by hydrogen bond interaction between OAPOSS and PNIPAM side chains (Figure ).…”
Section: Construction Of Poss-containing Hydrogelsmentioning
confidence: 99%
“…Scheme for the preparation of hydrogels based on OAPOSS and PNIPAM. [Reproduced with permission from ref . Copyright 2019, Wiley–VCH, Weinheim, Germany.…”
Section: Construction Of Poss-containing Hydrogelsmentioning
confidence: 99%
“…Xu et al reported temperature and pH dual-responsive hydrogels based on poly(N-isopropylacrylamide) (PNIPAM) and poly(dimethylaminoethyl methacrylate) co-crosslinked by octa-vinyl POSS and N,N′-methylenebisacrylamide (MBA), which exhibited improved compressive strength and a faster swelling/deswelling rate [ 29 ]. Zhang et al added octa-amino POSS into a PNIPAM system as an imitator and a physical crosslinker in the presence of a small amount of MBA, chemical crosslinker, which produced hydrogels that exhibit self-healing ability [ 30 ]. With respect to mono-functional POSS, Yang et al used POSS as an end-cap for blocking copolymers of PEG and bisuream.…”
Section: Introductionmentioning
confidence: 99%